Hydrophobic epoxy resin coating with ionic liquid conversion pretreatment on magnesium alloy for promoting corrosion resistance. (15th January 2020) - Guo, Liting; Gu, Changdong; Feng, Jie; Guo, Yongbin; Jin, Yuan; Tu, Jiangping
Abstract: A hydrophobic epoxy resin coating with an environmental-friendly deep eutectic solvent (DES)-based conversion pretreatment was proposed to enhance the corrosion resistance of magnesium alloys. The hydrophobic epoxy resin coatings on the AZ31B magnesium alloy with and without the DES-based conversion pretreatment were thoroughly compared. It is found that the DES-based conversion film on the AZ31B magnesium alloy is mainly composed of MgH2, MgO and MgCO3 . Furthermore, the conversion film possesses porous structure, which provides more anchor points for the following epoxy resin coating. However, without the DES-conversion pretreatment, the epoxy resin is difficult to be attached on the substrate during the dip-coating process. The double layered hybrid coating system promotes the corrosion resistance of the magnesium alloys significantly, which can be ascribed to the unique architecture and component including the hydrophobicity of the surface layer, the dense and interlocked epoxy resin, and the corrosion resistant DES-based conversion pretreatment.